(untitled) (Hoboken, N.J., 2008)
This hands-on, comprehensive reference provides accessible, organized information on the structures and applications of Vitamin D and its related chemicals. The most extensive published list of Vitamin D molecules, it provides a record for approximately 950 derivatives of Vitamins D2 and D3.
Keywords: Vitamin D,Vitamin D,Vitamin D,Vitamin D; Chemistry,Sổ tay, sách hướng dẫn, vv..,Hóa học